Tweaking palladium electronic structure to attain oxygen reduction activity superior to platinum/C - Sarma, Saurav Ch.; Kaja, Sai Manoj; Mishra, Vidyanshu; Vinod, Chathakudath Prabhakaran; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
Enhancing oxygen reduction (ORR) activity through alloying is crucial to improve the performance of a fuel-cell catalysts. In this work, we have studied the alloying effects of 4f rare-earth (RE) metals with palladium. The modified catalyst exhibits better activity (E-onset = 1 V and E-1/2 = 0.88 V) and higher selectivity toward H2O (similar to 97%) compared to the state-of-the-art catalysts due to complete dissociation of O-2. Hirshfeld charge analysis and 2D-electron localization function reveal improved adsorbate-adsorbent interaction on the catalyst surface. This work paves a strategy to design highly selective non-Pt-based catalysts for the ORR by controlling electronic structures and surface oxide formation.
Keywords: d-band center; DFT calculation; durability; EuPd; oxygen reduction reaction; YbPd

Tailoring COFs: transforming nonconducting 2D layered COF into a conducting quasi-3D architecture via interlayer knitting with polypyrrole - Jain, Chitvan; Kushwaha, Rinku; Rase, Deepak; Shekhar, Pragalbh; Shelke, Ankita; Sonwani, Disha; Ajithkumar, Thalasseril G.; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan (Journal of the American Chemical Society, 2023)
Improving the electronic conductivity and the structural robustness of covalent organic frameworks (COFs) is paramount. Here, we covalently cross-link a 2D COF with polypyrrole (Ppy) chains to form a quasi-3D COF. The 3D COF shows well-defined reflections in the SAED patterns distinctly indexed to its modeled crystal structure. This knitting of 2D COF layers with conjugated polypyrrole units improves electronic conductivity from 10(-9) to 10(-2 )S m(-1). This conductivity boost is affirmed by the presence of density of states near the Fermi level in the 3D COF, and this elevates the COF's valence band maximum by 0.52 eV with respect to the parent 2D pyrrole-functionalized COF, which agrees well with the opto-electro band gaps. The extent of HOMO elevation suggests the predominant existence of a polaron state (radical cation), giving rise to a strong EPR signal, most likely sourced from the cross-linking polypyrrole chains. A supercapacitor devised with COF20-Ppy records a high areal capacitance of 377.6 mF cm(-2), higher than that of the COF loaded with noncovalently linked polypyrrole chains. Thus, the polypyrrole acts as a ``conjugation bridge'' across the layers, lowering the band gap and providing polarons and additional conduction pathways. This marks a far-reaching approach to converting many 2D COFs into highly ordered and conducting 3D ones.
Keywords: covalent organic frameworks; Electrical conductivity